Cryptosporidium parvum infections in a cohort of veterinary students in Sweden - KINROSS, P. (Epidemiol Infect, 2015)
In March 2013, a veterinary student tested positive for Cryptosporidium; four classmates reported similar gastrointestinal symptoms. We aimed to identify source(s) and risk factors for Cryptosporidium infection in university persons symptomatic between 21 January and 14 April 2013. Sixty-four (79%) students from a cohort of 81 fourth-year veterinary students completed questionnaires, identifying 13 cases; four were Cryptosporidium parvum GP60 subtype IIaA16G1R1b, two were IIdA24G1, seven did not submit stool samples. Thirteen cases attended the university's field clinic before symptom onset (13/37 attendees, 35%); 11 visited at least one of four farms where students recalled seeing calves with diarrhoea. C. parvum subtype IIaA16G1R1b was identified in calves at one of the farms. Entering pens of calves with diarrhoea [relative risk (RR) 7·6, 95% confidence interval (CI) 1·7–33·5] and eating in clinic cars (RR 9·1, 95% CI 1·3–65·8) were associated with being a case. Washing hands at least twice per farm visit (0 cases, P = 0·03) was protective. This outbreak investigation was notable for rapid and effective collaboration between public health, veterinary and environmental sectors, leading to swift identification of a microbiological and epidemiological link between cases, infected calves and their farms. We recommend frequent hand-washing using proper technique and dissuasion from eating in clinic cars to minimize possible exposure to contaminated surfaces.